Step-by-step Vascular Control for Extracapsular Resection of Complex Giant Liver Hemangioma Involving the Inferior Vena Cava. Issue 1 (January 2014) - Dou, Lei; Meng, Wei-Shan; Su, Bao-Dong; Zhu, Peng; Zhang, Wei; Liang, Hui-Fang; Chen, Yi-Fa; Chen, Xiao-Ping
Massive hemorrhage remains an important clinical problem in extracapsular resection of giant liver hemangiomas (GLHs), especially for those involving the proximal hepatic veins and/or inferior vena cava. Between July 2004 and March 2012, 87 patients with a complex GLH scheduled for surgical treatment were included in this study. All patients were underwent vascular preparation (Step 1), advanced hepatic artery clamping (Step 2), and stepwise vascular occlusion (Step 3). Intraoperative blood loss, blood transfusion volume, degree of ischemia–reperfusion injury, and postoperative complications were recorded. No patients required urgent vascular preparation to manage intraoperative bleeding. In total, 87, 64, and 21 patients had portal triad (PT), infra-hepatic inferior vena cava (IVC), and suprahepatic IVC preparation; and 17, 43, and 11 patients had PT, PTand suprahepatic IVC, and all three (PT, infra-, and suprahepatic IVC) occlusions. The PT, infrahepatic IVC, and SIVC occlusion times were 12.1 ± 3.7 minutes, 7.9 ± 2.4 minutes, and 3.2 ± 1.4 minutes, respectively. Mean blood loss was 291.9 ± 124.5 mL, and only four patients received blood transfusions. No patients had life-threatening complications or died (Clavien-Dindo Grade 4, 5). Compared with paralleled studies, this technique has an advantage to decrease the blood loss in less liver ischemia time. For complex GLH resections, the described step-by-step vascular control technique was efficacious and feasible for controlling intraoperative bleeding.